Behavioral analysis of indicators related to the user profiles of the Mettzer platform - Halta dos Santos, Joana; Jeronimo de Macedo, Douglas Dyllon (Advanced Notes in Information Science, 2022)
This work addresses the usage of indicator analysis as a suitable alternative for applications in companies' most diverse business areas. We assumed that companies linked to the technology sector, such as the one in this study, permeate the construction of their organizational culture code and services among some data orientation factors. The perspective of indicators' analysis grows as a knowledge strategy in the company context and harvests each part of the business. This perspective also favors pieces of more significant assertive impact in actions such as increased productivity, cost reduction, and process optimization, such as the application in product and business metrics. The present work comprises the elaboration of the behavioral analysis of indicators related to the user's profiles of the Mettzer platform. This platform works integrated with the module for universities - as an opportunity search platform (Promotion Notices) and in another aspect, combined with the module for students - Text editor for formatting academic works, according to the Brazilian Association of Technical Norms (ABNT). The editor is the product that effectively contributes to the research carried out in this work, whose objective is to analyze the behavior patterns of the users' profiles of this module for possible application in product metrics. This paper is an exploratory, descriptive and qualitative research of a quantitative approach, in which we collected indicators from the text editor database. Our results sought to favor the company in improving actions to build a strategic differential. We obtained an overview of the behavioral relationships of indicators from the subscriber's profiles and test users, which, in turn, presented helpful information for the company and reaffirmed the trend of analyzing indicators as a good source for decision-making.